APLIKASI MARKET BASE ANALITIK UNTUK MEMPELAJARI POLA BELANJA MASYARAKAT PADA TOKO UD GARAM KUSTONO MENGGUNAKAN ALGORITMA APRIORI - Rizki Gunawan; Wildan Toyib (UHAMKA Press, 2023)
At this time the transaction data at the UD Garam Kustono store has decreased, this shows that there is an increase in sales competition followed by an increase in applying information technology. To overcome these problems, a very appropriate sales strategy is needed to use the availability of useful data and information. Data mining is a technique that can be used to process transaction data more efficiently. The method used by researchers is the a priori algorithm. The aim of this study is to apply a data mining system to find information on interrelationships between products that can support sales strategies from transaction data. The result of this study will show that the system built can run well, as evidenced by the result of the analysis using the Apriori algorithm, the system is able to find out the shape of the combination between product that have been found in previous sales. This information can assist in making decisions in developing product promotion strategies that will be offered to buyer.